UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT DILIHAT DARI SUDUT HAK ASASI MANUSIA - Eman Sulaiman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Human rights into public discourse since World War II, especially after the United Nations (UN), which was formed in 1945 managed to proclaim a general statement on Human Rights. The cornerstone of the establishment of the Law No. 18 Year 2003 concerning Advocates contrary to human rights, particularly the rights to justice. Substance Act No. 18 Year 2003 concerning Advocates violate human rights, especially the rights to justice in the form of obtaining legal assistance.